2019
DOI: 10.1200/po.19.00194
|View full text |Cite
|
Sign up to set email alerts
|

Basket Designs: Statistical Considerations for Oncology Trials

Abstract: Progress in the areas of genomics, disease pathways, and drug discovery has advanced into clinical and translational cancer research. The latest innovations in clinical trials have followed with master protocols, which are defined by inclusive eligibility criteria and devised to interrogate multiple therapies for a given tumor histology and/or multiple histologies for a given therapy under one protocol. The use of master protocols for oncology has become more common with the desire to improve the efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 49 publications
1
38
0
Order By: Relevance
“…While the naive pooling approach does not have a Bayesian equivalent in Tables 3 and 4, it can be noted that Kaizer et al demonstrated previously that it results in drastic inflation to the family-wise type I error rate for basket trials where the scenario is not the global null. 22 The simulation results for the trial with 10 indications are presented in the Supplementary Material (Supplementary Figures 1 and 2 for weighted marginal and family-wise type I error rates, respectively). Results with 10 indications demonstrate similar performance to trends observed for five indications.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the naive pooling approach does not have a Bayesian equivalent in Tables 3 and 4, it can be noted that Kaizer et al demonstrated previously that it results in drastic inflation to the family-wise type I error rate for basket trials where the scenario is not the global null. 22 The simulation results for the trial with 10 indications are presented in the Supplementary Material (Supplementary Figures 1 and 2 for weighted marginal and family-wise type I error rates, respectively). Results with 10 indications demonstrate similar performance to trends observed for five indications.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…demonstrated previously that it results in drastic inflation to the family-wise type I error rate for basket trials where the scenario is not the global null. 22…”
Section: Illustration Of Proposed Design Criteriamentioning
confidence: 99%
“…Several Bayesian solutions, developed for basket trials, offer opportunities to formalize the designs of large expansion cohorts and integrate the information across doseexpansion cohorts to facilitate evidence synthesis for planning the next phase of development. [69][70][71][72][73][74] CONCLUSIONS Classic 3+3 phase I trial designs have withstood the test of time. They offer rapid, but reasonable, dose escalation, with negligible rates of toxic death.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adjustment of multiplicity over the different subpopulations is required in planning basket trials. The manner of the adjustment of multiplicity depends on the purpose of the trial, 13,14 although there is currently no official regulatory framework 14 . Kaizer et al 13 suggested controlling the false‐positive rate in each subpopulation for exploratory settings, and overall family‐wise error rate in all subpopulation for confirmatory settings.…”
Section: Introductionmentioning
confidence: 99%